Let's Talk About Sex: The Social Determinants of Sexual and Reproductive Health for Second-Year Medical Students - Sarah E. Stumbar; Nana Aisha Garba; Cheryl Holder (Association of American Medical Colleges, 2018)
Introduction Sexual health is influenced by a myriad of social factors including health care access, social and cultural norms, insurance status, educational level and health literacy, economic status, sex, gender identity, and sexual orientation and behavior. It is pivotal to educate future physicians about these social determinants so that they can work to mitigate the resulting disparities and thereby improve the health of patients and their communities. Methods This 2-hour, large-group session for second-year medical students was first given in the fall of 2017. It included a 1-hour, case-based lecture followed by a patient panel. Panelists discussed their interactions with the medical system and how these related to their sex and gender identity. Ninety students (77.5% response rate) completed both pre- and postsurveys and an overall assessment of the session. Results Students reported high levels of satisfaction with the session. Eighty-seven percent felt they would benefit from more classes including a patient panel, and 93% reported specifically that the panel helped them to identify their own biases related to sexual orientation and gender. In the postsurvey, there was a significant (p < .05) increase in the number of students reporting increased comfort regarding various aspects of sexual history taking and interacting with patients of different sexual orientations and gender identities. Discussion This instructional format provided an effective way to teach medical students about the social determinants of sexual and reproductive health. Students both appreciated the session format and reported increased comfort and confidence related to the subject matter.